Comparative study on Young's modulus measurements on additively manufactured alloys - Lim, Gordon Yicai (Nanyang Technological University, 2024)
Additive manufacturing has advanced to a point where initial components are transitioning into practical use. Essential material properties including strength parameters and Young’s modulus are crucial for component designs. Young modulus, in particular, plays a fundamental role in material selection and design, as understanding the materials Young’s modulus allows engineers to accurately predict the behaviour of components and structures under applied loads.